Attenuation of Gifford-McMahon cryocooler induced vibration using mechanical vibration isolators. (September 2020) - Su, Ruifeng; E, Linzhongyang; Chen, Xueqian; Du, Qiang
Highlights: The MVIs induce the modal shapes and impact the induced vibration response. Structural parameters of the MIVs influence the vibration response. The influences are different with respect to the directions. The vibration response is attenuated through optimizing the installation sites. Abstract: Aiming to attenuate the vibration that is induced by a Gifford-McMahon (G-M) cryocooler, a method attenuating the vibration with mechanical vibration isolators (MVIs) is proposed. A scheme supporting the G-M cryocooler with one kind of supporting system that mainly comprises the MVIs is presented. The vibration response of the supporting system caused by the vibration of the G-M cryocooler are studied, and the effects of the structural parameters of the MVIs are investigated. The results show that reciprocating moving modes of the MVIs induce the modal characteristics of the supporting system, which further formed the vibration response of the supporting system under the excitation of the G-M cryocooler vibration. Structural parameters of stiffness and installation sites of the MVIs affect the reciprocating moving mode of the MVIs, through which the modal characteristics and the vibration response of the supporting system are affected. Through optimizing the installation sites of the MVIs, the vibration response of the supporting system is attenuated. It demonstrates that the method proposed in this paper is available for attenuating the cryocooler-induced vibration in the field of cryogenics and refrigeration.